2003
DOI: 10.1063/1.1627459
|View full text |Cite
|
Sign up to set email alerts
|

GaAs on Si heterostructures obtained by He and/or H implantation and direct wafer bonding

Abstract: Transfer of GaAs layers onto Si by helium and/or hydrogen implantation and wafer bonding was investigated. The optimum conditions for achieving blistering/splitting only after postimplantation annealing were experimentally obtained. It was found that specific implantation conditions induce large area exfoliation instead of blistering after annealing of unbonded GaAs. This effect is related to a narrow size and/or a depth distribution of the platelets in as-implanted GaAs and their evolution with annealing. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 24 publications
1
38
1
1
Order By: Relevance
“…Wafer bonding and layer transfer has now been applied to semiconductors other than silicon such as Ge, InP, GaAs, and GaN. [2][3][4][5][6] The mechanism of H-induced exfoliation has been extensively studied in the case of silicon, 7,8 and, more recently, in the case of InP. 9 The early work of Weldon et al provided important conclusions: ͑i͒ implantation induced defects serve to trap H within the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Wafer bonding and layer transfer has now been applied to semiconductors other than silicon such as Ge, InP, GaAs, and GaN. [2][3][4][5][6] The mechanism of H-induced exfoliation has been extensively studied in the case of silicon, 7,8 and, more recently, in the case of InP. 9 The early work of Weldon et al provided important conclusions: ͑i͒ implantation induced defects serve to trap H within the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was only recently shown that the concept of hydrogen-induced exfoliation can be applied to the transfer of thin films of InP and GaAs to foreign substrates. [6][7][8] Moreover, a detailed understanding of the role of H in these materials is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Что касается имплантации ионов водорода (протонов), то она может использоваться как для целенаправленного введения дефектов (в основном точечных) при небольших дозах имплантации, так и в так называемой Smart-Cut техно-логии для создания полупроводниковых структур с ди-электрической изоляцией. Последнее касается как наи-более распространенных структур кремний-на-изолято-ре (SOI) [4], германий-на-изоляторе (GeOI) [5], так и структур на основе сложных полупроводников [3], в том числе структур арсенид галлия на изоляторе (GOI) [6,7].…”
Section: Introductionunclassified